Pemberian Pupuk Kandang dan Tingkat Bumbunan terhadap Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L) - Abdul Razaq; Dirmawan Huitagaol; Aisyah Lubis (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2026)
Peanuts have significant potential for development in Indonesia due to their high economic value, which presents a significant market opportunity. A factorial randomized block design was chosen in the study with the provision of two factors studied and three replications. The two factors are the application of manure (L) at three levels (L0 = control, L1 = 2 kg plot-1, and L2 = 4 kg plot-1), and the formation of the level of hilling (B) as the second factor with four levels (B0 = control, B1 = 5 cm plant-1, B2 = 10 cm plant-1, and B3 = 15 cm plant-1). The parameters assessed included plant height (cm), number of filled pods per sample (g), and weight of filled pods per sample (g). The results showed that manure application had no significant effect on plant height, number of filled pods per sample, and weight of filled pods per sample. The level of hilling had no significant effect on plant height, number of filled pods per sample, and weight of filled pods per sample. The interaction between manure application and the level of hilling had no significant effect on all observed parameters.